Off-Label Drug Marketing, the First Amendment, and Federalism - David Orentlicher (Washington University Journal of Law & Policy, 2016)
This article focuses on the unique nature of prohibited disclosures within the health care field. Specifically, this article details the relationship between restrictions on off-label drug use advertising and constitutionally protected free speech. Orentlicher explores the conflict between regulation of off-label drug use through direct prohibition versus regulation through indirect advertising restrictions. Ultimately, Orentlicher argues that pharmaceutical companies should not be able to invoke first amendment arguments against off-label advertising restrictions due to the potential for harm to the consumer.
Keywords: First Amendment; Federalism; Free speech; Off-label drug marketing; Advertising; Regulation; FDA